2013
DOI: 10.1039/c3cc44199g
|View full text |Cite
|
Sign up to set email alerts
|

A spin-crossover ionic liquid from the cationic iron(iii) Schiff base complex

Abstract: A thermochromic magnetic ionic liquid containing a cationic iron(III) Schiff-base complex has been developed, whose color and magnetic moment change with temperature because of spin crossover in the liquid state. This spin-crossover behavior closely resembles that of a solid having the same cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…21 This change is different to that seen in spin crossover complexes 22 , where the transitions occur between high-spin and low-spin states, often also involving a transition from para-to diamagnetism. In the two ionic liquids discussed here both the high and low temperature states are paramagnetic with the change in effective magnetic moment reflecting the difference in orbital splitting, ∆ between the different coordination states, which governs the departure from the spin-only moment (see Figure 4).…”
Section: Temperature-dependent Switching Of Paramagnetism Of a Cobaltmentioning
confidence: 97%
“…21 This change is different to that seen in spin crossover complexes 22 , where the transitions occur between high-spin and low-spin states, often also involving a transition from para-to diamagnetism. In the two ionic liquids discussed here both the high and low temperature states are paramagnetic with the change in effective magnetic moment reflecting the difference in orbital splitting, ∆ between the different coordination states, which governs the departure from the spin-only moment (see Figure 4).…”
Section: Temperature-dependent Switching Of Paramagnetism Of a Cobaltmentioning
confidence: 97%
“…6 Interestingly, studies on paramagnetic MCILs predate those works, but were focused on other aspects of the materials, disregarding their magnetic properties. 7,8 Subsequent to these studies, the magnetic properties of MCILs started attracting more attention, with reports of MCILs containing mononuclear magnetic cations, [9][10][11][12][13][14][15][16] mononuclear magnetic anions [17][18][19][20][21][22][23][24][25] and one report on the magnetic properties of a triferric cationic MCIL. 26 Due to the mononuclear structures of the spin carriers in those magnetic MCILs, the tuning of their magnetic properties, when attempted, focused on modifications of the diamagnetic counterion; e.g., it was demonstrated that changing the countercation charge, two or three [FeCl 3 Br] anions could be assembled around it, yielding a higher magnetic moment per formula unit.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole-based ligands, in combination with other auxiliary ligands that coordinate to the metal center, have been shown to produce MILs with good hydrolytic stability. 20 The magnetic susceptibility of MILs can be largely tuned for a specific application by incorporating different paramagnetic metals into the chemical structure. [21][22][23] Mn(II) based MILs possess higher magnetic susceptibilities than Co(II) and Ni(II) MILs.…”
Section: Introductionmentioning
confidence: 99%